Contribution of the two domains of E. coli 5′‐nucleotidase to substrate specificity and catalysis. Issue 5 (17th January 2013) - Krug, Ulrike; Patzschke, Rica; Zebisch, Matthias; Balbach, Jochen; Sträter, Norbert
Abstract : Escherichia coli 5′‐nucleotidase, a two‐domain enzyme, dephosphorylates various nucleotides with comparable efficiency. We have expressed the two domains individually in E. coli and show by liquid state NMR that they are properly folded. Kinetic characterization reveals that the C‐terminal domain, which contains the substrate‐binding pocket, is completely inactive while the N‐terminal domain with the two‐metal‐ion‐center and the core catalytic residues exhibits significant activity, especially towards substrates with activated phosphate bonds (ATP, ADP, p‐nitrophenyl phosphate). In contrast, residues of the C‐terminal domain are required for efficient hydrolysis of AMP. Abstract : ► The N‐ and C‐terminal domains of E. coli 5′‐nucleotidase fold individually. ► Only the N‐terminal domain is catalytically active in absence of the other domain. ► The N‐terminal domain is responsible for the core catalytic steps. ► The C‐terminal domain provides the specificity for nucleotide substrates.